Service Quality and Promotion on The Customer Satisfaction CAFÉ AWOR - Jannah, Della Qoyimatul; Putra, Yudiarto Perdana; Gustiawan, Wahyu Dede (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
The rapid advancement of global business has impacted the coffee shop industry in Indonesia, including Awor Coffee, which has experienced rapid growth. The primary objective of this study is to thoroughly explore and dissect the influence of advanced service quality and promotional strategies on customer satisfaction levels at Café Awor. This research utilizes a quantitative research method. The sample for this study consists of customers who have engaged in transactions at Café Awor in the City of Kediri, with an unspecified population size and an advanced sample size of 100 individual. The sampling method utilized in this study is purposive sampling. The data analysis technique applied in this research is advanced multiple linear regression. Data manipulation in this study utilizes SPSS 23.. The outcomes of the t-test reveal that the service quality variable (X1) with a probability value of 0.00 < 0.05 implies that service quality significantly influences customer satisfaction on a partial level. The promotional factor (X2) with a probability value of 0.00 < 0.05 indicates that promotion exerts a substantial partial influence on customer satisfaction. The concurrent examination findings, indicating an F-value of 98.664 > F-table 3.09 (98.664 > 3.09), demonstrate a significant result. The F-test outcome displays a significance value of 0.000, falling below α 0.05 (0.000 < 0.05). Consequently, the null hypothesis (H0) is dismissed while the alternative hypothesis (Ha) is upheld, denoting a noteworthy concurrent influence of service quality (X1) and promotion (X2) on customer satisfaction (Y) at Café Awor located in Kediri City. Keywords : service quality, promotion, customer satisfaction